Solution-processed zirconium acetylacetonate charge-trap layer for multi-bit nonvolatile thin-film memory transistors - Song Lee; Jeong-In Lee; Chang-Hyun Kim; Jin-Hyuk Kwon; Jonghee Lee; Amos Amoako Boampong; Min-Hoi Kim (Science and Technology of Advanced Materials, 2023)
ABSTRACTThe charge trap property of solution-processed zirconium acetylacetonate (ZAA) for solution-processed nonvolatile charge-trap memory (CTM) transistors is demonstrated. Increasing the annealing temperature of the ZAA from room temperature (RT) to 300°C in ambient, the carbon double bonds within the ZAA decreases. The RT-dried ZAA for the p-type organic-based CTM shows the widest threshold voltage shift (∆VTH ≈ 80 V), four distinct VTHs for a multi-bit memory operation and retained memory currents for 103 s with high memory on- and off-current ratio (IM,ON/IM,OFF ≈ 5Ⅹ104). The n-type oxide-based CTM (Ox-CTM) also shows a ∆VTH of 14 V and retained memory currents for 103 s with IM,ON/IM,OFF ≈ 104. The inability of the Ox-CTM to be electrically erasable is well explained with simulated electrical potential contour maps. It is deduced that, irrespective of the varied solution-processed semiconductor used, the RT-dried organic ZAA as CTL shows the best memory functionality in the fabricated CTMs. This implies that the high carbon double bonds in the low-temperature processed ZAA CTL are very useful for low-cost multi-bit CTMs in flexible electronics.